The need for an alternative method to determine intravascular volumes. Issue 9 (21st October 2018) - Lobigs, L. M.; Peeling, P.; Dawson, B.; Schumacher, Y. O.
Abstract: It is well described that numerous environmental factors, including exercise, modulate plasma volume (PV). These modulations prove problematic when a number of haematological markers are measured as a concentration in blood plasma. A primary example is haemoglobin concentration ([Hb]), a marker of erythropoiesis commonly used within medicine and also used to detect blood doping. Natural changes in PV can confound [Hb] values when a volume change is detected rather than a true change in haemoglobin mass (Hbmass ) (e.g. volume expansion resulting in a [Hb] decrease and pseudo-anemia vs. Hbmass decline resulting in anaemia). Currently, there is no simple solution to correct for PV shifts, and this has proven problematic when monitoring volumetric health markers in clinical and anti-doping settings. This narrative review explores the influence that PV shifts have on volumetric biomarkers, such as [Hb]. The progressive expansion in PV observed during multi-day endurance events will be summarised, and the observed impact PV variance has on concentration-based markers will be quantified. From this, the need for alternative methods to correct [Hb] for volume fluctuations is highlighted. Available methods for calculating intravascular volumes are then discussed, with a focus on a recently developed approach using a panel of 'volume descriptive' biomarkers from a standard blood test. Finally, the practical applications of this novel PV blood test within both anti-doping and clinical settings will be examined.